2018
DOI: 10.1021/acsomega.8b01856
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Phytoactive Molecules on Transcriptional Expression, Biofilm Matrix, and Cell Wall Components of Candida glabrata and Its Clinical Isolates

Abstract: Toxicity challenges by antifungal arsenals and emergence of multidrug resistance scenario has posed a serious threat to global community. To cope up with this alarming situation, phytoactive molecules are richest, safest, and most effective source of broad spectrum antimicrobial compounds. In the present investigation, six phytoactive molecules [cinnamaldehyde (CIN), epigallocatechin, vanillin, eugenol (EUG), furanone, and epigallocatechin gallate] were studied against Candida glabrata a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 90 publications
(179 reference statements)
3
65
0
Order By: Relevance
“…OD at 530 nm was measured at 0 and 48 h after incubation. The proportion of the inhibition of biofilm proliferation was based on the reduction between the OD at 48 h and the OD at 0 h, as following: [(ODr control) -(ODr treated)/(ODr control)], where ODr = [OD at 48 h-OD at 0 h] (Gupta et al, 2018). The experiments were performed in triplicate.…”
Section: Effect On the Growth Rate Of Preformed Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…OD at 530 nm was measured at 0 and 48 h after incubation. The proportion of the inhibition of biofilm proliferation was based on the reduction between the OD at 48 h and the OD at 0 h, as following: [(ODr control) -(ODr treated)/(ODr control)], where ODr = [OD at 48 h-OD at 0 h] (Gupta et al, 2018). The experiments were performed in triplicate.…”
Section: Effect On the Growth Rate Of Preformed Biofilmsmentioning
confidence: 99%
“…Coumarins represent a diverse group of natural polyphenols found in a variety of plants and known by their varied pharmacological properties (Reviewed in Kostova et al, 2011 ; Pinto and Silva, 2017 ; Tomasz Kubrak et al, 2017 ). Scopoletin is one type of coumarin with promising biological activities including antioxidant ( Jamuna et al, 2015 ; Zhang et al, 2017 ), anti-inflammatory ( Jamuna et al, 2015 ; Leema and Tamizhselvi, 2018 ), anti-aging ( Jamuna et al, 2015 ) and anti-tumoral ( Pinto and Silva, 2017 ; Gupta et al, 2018 ) effects.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting report with terpene cinnamaldehyde showed its fungicidal activity against C. glabrata isolates, demonstrating reduced expression of the FKS1 gene responsible for β-1,3-glucan biosynthesis. However, in that study, the content of extracellular carbohydrates was actually observed to increase [ 89 ]. On the other hand, a different course of action for β-1,3-glucan reduction by poacic acid was reported in several Candida spp.…”
Section: A New Perspective For Plants’ Components In Antifungal Thmentioning
confidence: 98%
“…On the other hand, essential oils of Cinnamomum verum and Pelargonium graveolens rich in terpenes and phenylpropanoids were able to act synergistically with fluconazole, resulting in membrane destabilization due to reduced ergosterol biosynthesis and disturbed fatty acid homeostasis in C. albicans cells [ 96 ]. Gupta and co-workers [ 89 ] also demonstrated the reduction of ergosterol synthesis in C. glabrata isolates by another terpene–cinnamaldehyde, due to a decreased expression of gene encoding enzymes involved in ergosterol synthesis in the cell membrane ( ERG2, ERG3, ERG4, ERG10, ERG11 ) and gene encoding ABC transporters ( CDR1 ).…”
Section: A New Perspective For Plants’ Components In Antifungal Thmentioning
confidence: 99%
See 1 more Smart Citation